3D structured illumination microscopy of mammalian embryos and spermatozoa. Issue 1 (December 2015) - Popken, Jens; Dahlhoff, Maik; Guengoer, Tuna; Wolf, Eckhard; Zakhartchenko, Valeri
Abstract Background Super-resolution fluorescence microscopy performed via 3D structured illumination microscopy (3D-SIM) is well established on flat, adherent cells. However, blastomeres of mammalian embryos are non-adherent, round and large. Scanning whole mount mammalian embryos with 3D-SIM is prone to failure due to the movement during scanning and the large distance to the cover glass. Results Here we present a highly detailed protocol that allows performing 3D-SIM on blastomeres of mammalian embryos with an image quality comparable to scans in adherent cells. This protocol was successfully tested on mouse, rabbit and cattle embryos and on rabbit spermatozoa. Conclusions Our protocol provides detailed instructions on embryo staining, blastomere isolation, blastomere attachment, embedding, correct oil predictions, scanning conditions, and oil correction choices after the first scan. Finally, the most common problems are documented and solutions are suggested. To our knowledge, this protocol presents for the first time a highly detailed and practical way to perform 3D-SIM on mammalian embryos and spermatozoa.